2020
DOI: 10.1177/2041669520927038
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenal Causality and Sensory Realism

Abstract: One of the most important tasks for humans is the attribution of causes and effects in all wakes of life. The first systematical study of visual perception of causality—often referred to as phenomenal causality—was done by Albert Michotte using his now well-known launching events paradigm. Launching events are the seeming collision and seeming transfer of movement between two objects—abstract, featureless stimuli (“objects”) in Michotte’s original experiments. Here, we study the relation between causal ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…To make an illustrative example, since Michotte’s (1946/1963) seminal study on the perception of causality, the intuitive physics of collisions has been mainly studied using simple animations involving immaterial shapes moving in one or two dimensions (e.g., Gerstenberg et al, 2012; Lau & Brady, 2020; Runeson & Vedeler, 1993; Sanborn et al, 2013; Smith & Vul, 2013; Vicovaro et al, 2020; White, 2007). Only few studies have attempted to increase the realism of simulated collisions, for instance by using 3D spheres made of definite simulated materials (Vicovaro, 2018; Vicovaro & Burigana, 2016) or by mimicking the effects of friction and rotation on the collision behavior of the stimuli (Meding et al, 2020; Reitsma & O’Sullivan, 2009). The results of these studies suggest that the realism of the stimuli has a substantial influence on subjective judgments of the naturalness of collisions.…”
Section: The Heuristic Perspectivementioning
confidence: 99%
“…To make an illustrative example, since Michotte’s (1946/1963) seminal study on the perception of causality, the intuitive physics of collisions has been mainly studied using simple animations involving immaterial shapes moving in one or two dimensions (e.g., Gerstenberg et al, 2012; Lau & Brady, 2020; Runeson & Vedeler, 1993; Sanborn et al, 2013; Smith & Vul, 2013; Vicovaro et al, 2020; White, 2007). Only few studies have attempted to increase the realism of simulated collisions, for instance by using 3D spheres made of definite simulated materials (Vicovaro, 2018; Vicovaro & Burigana, 2016) or by mimicking the effects of friction and rotation on the collision behavior of the stimuli (Meding et al, 2020; Reitsma & O’Sullivan, 2009). The results of these studies suggest that the realism of the stimuli has a substantial influence on subjective judgments of the naturalness of collisions.…”
Section: The Heuristic Perspectivementioning
confidence: 99%
“…Previous studies on material perception have shown that image speed and/or playback speed of video clips were strong determinants of apparent heaviness and stiffness (Shim et al, 2009;Kawabe et al, 2015;Kawabe and Nishida, 2016;Bi et al, 2018). In visual stimuli inducing perceptual causality (Michotte, 1963;Scholl and Tremoulet, 2000;Meding et al, 2020;Wang et al, 2020), movement speeds after object collision determine the perceived heaviness of the object (Todd and Warren, 1982). A previous study (Kawabe et al, 2021) showed that a lower speed of a cursor controlled by a participant's keystroke caused a stronger sense of resistance, while the resistance sensation produced by visual processing is not necessarily linked to the participant's action.…”
Section: Introductionmentioning
confidence: 97%